Peri-Traumatic Distress and Its Relationship to Resilience and Coping Among Medical Students in Malaysia During COVID-19 Lockdown - Mohamed, Salina; Ismail, Zaliha; Shuib, Norley; Ali, Nur Faizah (Frontiers in Psychiatry, 2021)
Background: Medical students are not spared from the challenges related to the Covid-19 lockdown. The fear and uncertainties may lead to traumatic symptoms and test their resilience and sense of coping. Thus, this study aims to determine the prevalence of peri-traumatic distress symptoms and its association with the level of resilience and the coping strategies used during the lockdown among medical students. Materials and Methods: This was a cross-sectional online questionnaire survey involving medical students from a public university in Malaysia. It was conducted during the COVID-19 lockdown or Movement Control Order (MCO) where the students were asked to fill in the COVID-19 Peri-traumatic Distress Index (CPDI), Brief COPE Inventory, and Connor Davidson Resilience Scale (CDRS-25). Results: A total of 282 clinical and 172 pre-clinical medical students were involved. Peri-traumatic distress symptoms were reported by 27% out of the total students. This study found that those who were having peritraumatic distress symptoms were from the pre-clinical years, had poor internet access, as well as lower resilience levels, and used more dysfunctional coping strategies. Pre-clinical medical students with difficult internet access were eight times more likely to have peritraumatic distress symptoms. Conclusions: Given the high level of peri-traumatic distress symptoms reported by medical students during the lockdown, it is vital to identify the vulnerable students, assess their needs and risks to mental health problems during this challenging time as the pandemic is still ongoing with countries going in and out of lockdown depending on the cases at the time. The university administration for each University in Malaysia will need to have a clear academic guideline and policy as well as providing improved infrastructure to minimize the distress faced by medical students.